INNOVATIVE TECHNOLOGIES IN THE INTERNATIONAL HOTEL INDUSTRY - Liutak О.М.; Baula , O.V.; Baula , V.V. (The actual problems of regional economy development, 2023)
The purpose of the article is to solve the scientific task of identifying the features of the modern level of use of innovative technologies in the hotel industry; systematization of high-tech innovations, which are the most likely trends in the near future for the hotel industry; identifying types of innovative strategies in international business and outlining opportunities and threats in their implementation. The following general scientific methods are the methodological basis of this research. The method of analysis and synthesis - when identifying the features of the modern level of use of innovative technologies in the hotel industry; method of systematization and generalization - when systematizing high-tech innovations, which are the most likely trends in the near future for the hotel industry; the method of scientific abstraction and explication - for distinguishing types of innovative strategies in international business and outlining opportunities and threats in their implementation. It has been found that today most of the hotels most often use such high-tech innovations as: power management systems, hotel internal services management system, improved room service technology and self-service technology as an innovation in the hotel industry, visual information display system, augmented / virtual reality, artificial intelligence in the field of hospitality, innovative tools for managing work processes in the hospitality industry, "social listening" and the sharing economy, etc. The article proves that in the hotel business, radical innovations are most often introduced, from which evolutionary branch organizational, economic and socio-cultural innovations subsequently emerge. The effects of innovation should include economic, scientific and technical, social and environmental effects, since it is on these environments that the hotel business exerts the greatest influence. Types of innovative strategies in international business, as well as opportunities and threats of their implementation are considered. The results of the study can be useful for the development of scientifically based recommendations for the implementation of innovative technologies in the hotel industry.